Diagnostic yield of combined ACR TI-RADS and Sonoelastography in solid thyroid nodules in tertiary care center: an analytical study - Dhakal, Saubhagya; Katwal, Shailendra; Paudel, Sharma; Yadav, Birendra Kumar (Journal of Karnali Academy of Health Sciences, 2026)
Background: Thyroid nodules are prevalent, and accurate differentiation between benign and malignant nodules is crucial for management. We aim to evaluate the effectiveness of combining Thyroid Imaging Reporting and Data System (TIRADS) scoring with strain elastography, specifically the Elasticity Contrast Index (ECI), to differentiate between benign and malignant thyroid nodules.Methods: This analytical cross-sectional study involved 77 patients with solid thyroid nodules identified through B-mode ultrasonography. ACR TI-RADS scores, ECI values, and combined scores were compared with Fine needle aspiration Cytology (FNAC) results. Statistical analysis was performed using SPSS, and Pearson correlation tests were conducted to assess the correlation with FNAC findings.Result: The TI-RADS scoring system has a sensitivity of 83.3%, a specificity of 66.1%, and a positive predictive value of 42.9% for distinguishing benign and malignant nodules. Strain elastography with ECI values has a sensitivity of 94.4%, specificity of 98.3%, PPV of 94.4%, and NPV of 98.3%. Combining ACR TI-RADS and strain elastography achieves a sensitivity of 100%, specificity of 66.1%, NPV of 100%, and PPV of 47.4%.Conclusion: The study emphasizes the benefits of integrating noninvasive methods like ultrasound elastography and ACR TI-RADS for improved diagnostic precision, minimizing invasion and patient discomfort. This strategy is particularly advantageous for TI-RADS 3 nodules and reduces unnecessary procedures. However, FNAC should be reasonable and validated for higher classifications.